Ambidexterity and Leadership Agility in Micro, Small and Medium Enterprises (MSME)'s Performance: An Empirical Study in Indonesia - Gatot Kustyadi, - (Korea Distribution Science Association (KODISA), 2021)
Ambidexterity and leadership agility have become the most researched topics to analyze their application in companies, especially in this dynamic era. Several researchers have analyzed it in large companies. However, only a few have discussed the two topics simultaneously and at the MSME level. This study aims to analyze the relationship between ambidexterity and leadership agility and innovation capability and performance at MSMEs in Yogyakarta and East Java, Indonesia. This study is analyzed by using quantitative methods with SEM (Structural Equation Model) methods. The data in this study is primary data that is obtained through distributing 230 questionnaires to MSME managers in Yogyakarta and East Java, Indonesia. From 230 questionnaires distributed, 200 questionnaires are returned and completed, so the response rate in this study is 86%. The results in this study indicate that ambidexterity and leadership agility have a significant effect on innovation capability and MSME performance. This study also proved that innovation capability has a significant effect on MSME performance. Therefore, it is recommended for MSME managers to develop ambidexterity and leadership agility so they can create innovation and good performance. In the end, this study has provided findings related to the combination of ambidexterity and leadership agility variables.